Changes in IgE binding capacity, structure, physicochemical properties of peanuts through fermentation with Bacillus natto and Lactobacillus plantarum along with autoclave pretreatment. (30th October 2022) - Pi, Xiaowen; Fu, Guiming; Yang, Yili; Wan, Yin; Xie, Mingyong
Highlights: Fermentation induced the degradation and structural changes in peanut proteins. Protein degradation and structural changes caused the reduction of allergenicity. The changes in physicochemical properties were observed in fermented peanuts. Fermentation had the potential to produce hypoallergenic peanut products. Abstract: This study investigated the immunoglobulin E (IgE) binding capacity, structure, and physicochemical properties of raw crushed peanut (RCP) after fermentation with Lactobacillus plantarum and Bacillus natto along with autoclaved pretreatment. SDS–PAGE showed the disappearance of partial protein (>45 kDa) in autoclaved peanuts (ACP) and fermented autoclaved peanuts with L. plantarum (LP), and of majority protein (>14.4 kDa) in fermented autoclaved peanuts with B. natto (BN) or a mixture of L. plantarum and B. natto (LPBN). Structural analysis revealed protein-aggregation and protein-unfolding in autoclaved and fermented peanuts, respectively. Indirect ELISA demonstrated that the IgE binding capacities in ACP, LP, BN and LPBN were reduced by 11.3%, 20.6%, 78.7% and 90.2%, respectively, compared to RCP. LPBN showed the lowest IgE binding capacity due to the highest masking and destruction of epitopes and exhibited the desirable physicochemical properties simultaneously. Mixed strain fermentation has the potential to produce hypoallergenic peanut products.